(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Pectin, a spontaneously occurring carbohydrate, has grown in importance in previous decades. Because of its biodegradability, scientists and consumers are increasingly appreciating the advantages of natural pectin. The dimethyl ester of polygalacturonic acids is pectin. Dried fruits and apple pomace are commercially extracted under moderately acidic circumstances. On the grounds of the degree of esterification, pectins are classified into two main categories. The development of three-dimensional networks, or gels, is caused by the connection of pectin chains. Pectin was used in the pharmaceutical business, as well as health promotion and treatment, because of its gelling characteristics. Tablets, gel beads, and film-coated dosage forms have all been explored as possible carriers for drug administration to the gastrointestinal system. The essential chemistry and general characteristics of pectin, as well as its gel formation process and properties, will be discussed in this study. Pectin will be used as an example in the pharmaceutical industry.